Target-Decoy with Mass Binning: A Simple and Effective Validation Method for Shotgun Proteomics Using High Resolution Mass Spectrometry - Joo, Jong Wha J.; Na, Seungjin; Baek, Je-Hyun; Lee, Cheolju; Paek, Eunok (AMER CHEMICAL SOC, 2010)
Shotgun proteomics using mass spectrometry (MS) has become the choice for large-scale peptide and protein identification. The recent development of high-resolution mass spectrometers such as FT-ICR or Orbitrap makes it possible to identify peptides within only a few parts per million (ppm), and it is expected to dramatically improve performance of peptide identification, as compared to low-resolution instruments. To fully exploit such significantly higher mass accuracy, however, appropriate data analysis methods are required. Here, we present a new target-decoy strategy, called Target-Decoy with Mass Binning, utilizing high mass accuracy for peptide identification validation, which remains a challenging problem in MS-based proteomics. When tested on various high-resolution MS data, our method was very effective and yet simple and showed comparable or better performance when compared with other validation methods.
Keywords: PEPTIDE IDENTIFICATION; SEQUENCE DATABASES; SEARCH STRATEGY; ACCURACY; MODEL